1988
DOI: 10.1136/adc.63.10_spec_no.1126
|View full text |Cite
|
Sign up to set email alerts
|

Transient hyperoxia and cerebral blood flow velocity in infants born prematurely and at full term.

Abstract: SUMMARY Little is known about the effects of hyperoxia on the cerebral circulation of human infants. Using duplex Doppler we measured the changes in cerebral blood flow velocity in a group of full term (n=15) and premature infants (n=17, median gestational age 31 weeks) in response to a transient threefold increase in oxygen tension. Measurements of blood gas tensions as well as blood pressure and cerebral blood flow velocity were made over a period of 20 minutes on three occasions for each infant; during norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
42
0
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 12 publications
3
42
0
1
Order By: Relevance
“…This was also expected since similar changes in PaO 2 have much smaller effects on the cerebral vasculature than changes in PaCO 2 . 34 Despite that a majority of previous studies also observed CBF increases, a few investigators reported decreases, 9,10 or brief decreases followed by increased CBF after suctioning. 15,16 One of the studies reporting CBF decreases had few patients, and the other had a majority of infants with IVH.…”
Section: Discussionmentioning
confidence: 94%
“…This was also expected since similar changes in PaO 2 have much smaller effects on the cerebral vasculature than changes in PaCO 2 . 34 Despite that a majority of previous studies also observed CBF increases, a few investigators reported decreases, 9,10 or brief decreases followed by increased CBF after suctioning. 15,16 One of the studies reporting CBF decreases had few patients, and the other had a majority of infants with IVH.…”
Section: Discussionmentioning
confidence: 94%
“…A couple of studies have documented a fall in CBFV in premature infants with hyperoxemia (24,25). Niijima et al observed a fall in CBFV in 88% premature infants in response to a transient threefold increase in oxygen tension (24). Leahy et al, by using a modified venous occlusion plethysmography technique, observed significant decrease in CBF in premature neonates after inhalation of 100% oxygen (25).…”
Section: Discussionmentioning
confidence: 98%
“…Excessive hyperoxia can cause a decrease in CBFV in human newborn infants but not with as strong an effect as hypocarbia. 18 We adjusted the inspired oxygen concentration immediately after surfactant administration to prevent an excessively high PAO 2 . Because we obtained measurements at 5 minutes after surfactant, it is possible that we missed significant CBFV changes if they occurred.…”
Section: Discussionmentioning
confidence: 99%